2017
DOI: 10.1017/s0047404517000616
|View full text |Cite
|
Sign up to set email alerts
|

The role of the descriptor ‘broken English’ in ideologies about nonnative speech

Abstract: This study investigates how the descriptor ‘broken English’ is used to construct speakers as nonnative within standard language ideology. In-depth analysis of examples found through WebCorp, used to search US websites, and the Corpus of Contemporary American English found that the term was largely used to refer to comprehensible English identified as nonnative. Users of such English were constructed as Other, usually highly negatively. The rarer cases of more positive descriptions referred to encounters outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, high perceived attractiveness, alongside an expectation of accentedness, may have combined to offer an attentional benefit for Picture A in particular, leading to better memory. Indeed, Lindemann and Moran () show that positive evaluations of accentedness emerge when accorded to non‐native English speakers that listeners may evaluate as “distantly superior.” Given that Picture A was frequently identified as attractive and even a celebrity (actor or pop star) in norming, a particularly positive assessment of “non‐nativeness” via an affordance of “distant superiority” may have been induced. The marginal correlation between better memory performance and higher perceived social attractiveness of the speaker across conditions (Table ) offers further support for this explanation.…”
Section: Discussionmentioning
confidence: 99%
“…However, high perceived attractiveness, alongside an expectation of accentedness, may have combined to offer an attentional benefit for Picture A in particular, leading to better memory. Indeed, Lindemann and Moran () show that positive evaluations of accentedness emerge when accorded to non‐native English speakers that listeners may evaluate as “distantly superior.” Given that Picture A was frequently identified as attractive and even a celebrity (actor or pop star) in norming, a particularly positive assessment of “non‐nativeness” via an affordance of “distant superiority” may have been induced. The marginal correlation between better memory performance and higher perceived social attractiveness of the speaker across conditions (Table ) offers further support for this explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Inner Circle social and political spaces are known to be notoriously intolerant of linguistic difference (Bonfiglio, 2002; Cameron, 2012; González & Melis, 2000; Lindemann & Moran, 2017; Lippi‐Green, 2012; Miller, 2011; Subtirelu, 2013). Ambivalence toward language difference is especially prevalent in Inner Circle academic contexts guided by ideologies of monolingualism, where students are expected to demonstrate proficiency in standardized norms of English (Alvarez & Lee, 2020; Flores & Rosa, 2015; Lee & Rice, 2007; Matsuda, 2006; Mazak & Carroll, 2017; Paris & Alim, 2017).…”
Section: China English In An Inner Circle Academic Contextmentioning
confidence: 99%
“…A recent study of the use of the term 'broken English' across two large corpora similarly found that this descriptor was more likely to be applied to low-status persons, and in texts presenting these individuals in a negative light, or with suspicion (Lindemann & Moran, 2017) Therefore, while Abyan's linguistic resources may impact the way her identity is perceived by her audience, her identity resources may also impact the way her communication is…”
Section: ) Explainsmentioning
confidence: 99%